Early vascular healing following bioresorbable-polymer sirolimus-eluting stent implantation in comparison with durable-polymer everolimus-eluting stent: sequential optical coherence tomography study. (25th November 2020) - Ogura, K; Tsujita, H; Arai, T; Sakai, R; Tanaka, H; Masaki, R; Oishi, Y; Nomura, K; Arai, K; Sekimoto, T; Kondo, S; Tsukamoto, S; et al.
Abstract: Background: Orsiro ultrathin-strut bioresorbable-polymer sirolimus-eluting stent (BP-SES) might facilitate early vascular healing responses that seems to be associated with improved long-term clinical outcomes. We compared the early vascular healing responses to BP-SES and Xience durable-polymer everolimus-eluting stent (DP-EES) in patients with chronic coronary syndrome (CCS) using optical coherence tomography (OCT). Methods: A total of 40 patients with CCS receiving OCT-guided PCI were included. 20 patients were assigned to BP-SES, and 20 to DP-EES. OCT was performed immediately after stent placement (post-procedure) and at 1 month follow-up. Struts were recorded as uncovered if any part was visibly exposed in the lumen or covered if a layer of tissue covered all reflecting surfaces. The incidence of intrastent thrombus (IS-Th) and irregular protrusion (IRP) were also assessed. Results: At 1 month, the percentage of uncovered struts was significantly lower in the BP-SES compared with the DP-EES (2.8±1.6% vs. 5.8±1.8%, respectively; p<0.001), and that of malapposed struts was similar between both groups (2.5±3.1% vs. 2.4±2.2%; p=0.76). There were no differences in the incidence of IS-Th (65.0% vs. 55.0% at post-procedure; p=0.54, 30.0% vs. 35.0% at 1 month; p=0.75) and IRP (30.0% vs. 25.0% at post-procedure; p=0.74). IRP had completely resolved at 1 month in both groups. Conclusion: Early vascular healing response to Orsiro BP-SES implantation was revealed in CCS patients at 1 month compared with Xience DP-EES. Orsiro BP-SES may have a potential to shorten the dual antiplatelet therapy duration. Funding Acknowledgement: Type of funding source: None